Antitubercular activity of thioseniicarbazones and semicarbazones - Mishra V.; Pandeya S.N.; Ananthan S. (My University, 2025)
Thiosemicarbazones and semicarbazones of (±) 3-menthone and aminoacetophenone have been prepared and screened for antitubercular activity. The MIC has been compared against rifampin and clarithromycin vs. M. tuberculosis. Compound 8 has shown more than 90% inhibition against M tuberculosis and M. avium (MIC more than 12.5μg/ml).